The Perceptions of the Pre-service and In-service Biology Teachers on Artificial Intelligence in Biology Learning - Kurniawan, Aditya; Hariyadi, Slamet; Prabowo, Abram Setyo; Savira, Nadyatul Ilma Indah (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aimed to determine the perceptions of pre-service biology teachers and in-service biology teachers on artificial intelligence in Biology learning. AI has recently become a new trend and has changed many aspects of life. Artificial intelligence allows machines to learn from experience, adapt to new inputs, and perform human-like tasks like ChatGPT, launched in Q4 of 2022. The survey method used in this study. We used a questionnaire from 42 respondents of in-service teachers and pre-service teachers, respectively. Selected teachers were senior high school biology teachers who have used the independent curriculum in their schools. This study showed that the pre-service biology teachers (69%) had higher perceptions than in-service biology teachers (40.5%). This result followed by AI usage; 28.6% of pre-service biology teachers and 7.1% of in-service biology teachers used AI daily. However, the pre-service and in-service biology teachers believed that AI could be implemented in the new curriculum to increase student achievement on biology subject. This study concluded that the perceptions of to use AI is still low. So, AI must be introduced to the pre-service and in-service biology teachers.